(untitled) (ҚазҰУ хабаршысы. Экономика сериясы, 2017)
All dynamic processes in the employment sector of the Kazakhstan labor market requires reassessment and revision of the structure of employment and the adoption of appropriate measures to foster employment, including self-employment in a market economy. These measures should ensure economic development of the country and at the same time to some extent, social protection of the population. In modern conditions, i.e. in the light of market economy development, economic relations, activities of the employed population in the Republic of Kazakhstan has created new types of employment or has a new flexible forms of employment, of employment of people in the economic environment of the country. And one of these forms of employment – this self-employment. The phenomenon of self-employment and its lack of theoretical research, regional feature development actualizes the content of the article. In a market economy, people adapt to the democratization, autonomy, and accordingly develop their abilities by engaging in the field of entrepreneurship looking for sources of income in this area was born the self-employed. The article describes the main directions of development of self-employment in the Kazakh labour market.